Ceramics and ceramic coatings in orthopaedics. Issue 16 (December 2015) - McEntire, B.J.; Bal, B.S.; Rahaman, M.N.; Chevalier, J.; Pezzotti, G.
Abstract: Advanced bioceramics have played integral roles in treatment modalities for damaged or diseased human joints and osseous defects. This paper reviews the uses and properties of ceramics and ceramic coatings variously employed as articulation devices in hip, knee, shoulder, and other joints, either as self-mated surfaces, or against polyethylene (both conventional and highly cross-linked versions), or for osseous- fixation as arthrodesis devices, bone scaffolds, and substitutes in the spine or extremities. The modern uses of oxide and non-oxide materials in these applications will be discussed, followed by an assessment and comparison of their mechanical and physicochemical properties. Recent developments in new bioceramic materials and composites along with advanced processing and testing methods are presented. Advanced bioceramics and coatings are expected to have increasing use in orthopaedics because of their unique combination and range of properties including strength and toughness, hardness and wear resistance, biocompatibility, bacteriostasis, and osseointegration.